The Meaning of Patience in the Koran (Charles Sandres Peirce Semiotic Analysis) - Luci Intan Sari (al-Afkar, Journal For Islamic Studies, 2024)
Patience is one of the noble morals that every Muslim must have. So far, patience is often said to be an attitude of restraint from all the trials that God has given him. However, in the Qur'an, patience has a broad meaning. This research aims to find signs of the word patience found in several verses in the Qur'an using a semiotic approach. The author himself uses Charles Sanders Peirce's semiotic theory, namely trichotomy (representation, object and interpretant) to reveal the meaning of patience in the Qur'an which is used as a sign. The research method used is qualitative content analysis, namely research that aims to identify the message of a media as the object of research. The results of this research show that patience is not only interpreted as an attitude to refrain from every trial, but also means patience in enduring suffering, patience with someone's unjust actions, patience with people who deny as experienced by the Prophet Ulul Azmi, patience so as not to be sad and anxious, patiently refrain from something that is hated, patiently advise each other over all obstacles, and patiently advise each other in goodness. According to the author, this research still needs to be developed in order to expand the study of the Qur'an, especially regarding the meaning of patience in other verses in the Qur'an.